미세플라스틱 표면에 형성된 담수 유래 생물막 군집 고찰 - 최우단; 히엔 티 뉴옌; 김은주; 조경진 (대한상하수도학회, 2022)
Recently microplastic (MP) biofilm is being attracted as an important environmental issue because it can act as a pollutant carrier in aqueous system. Therefore, this study investigated the MP biofilm communities originated from freshwater. The results showed the bacterial community structure of MP biofilm was distinctively different from the freshwater regardless of biofilm-forming condition and MP type. For MP biofilm communities exposed to raw freshwater, Solimonas variicoloris-like microbe, Frigidibacter albus-like microbe, Nitrospirillum amazonense-like microbe, and Pseudochroococcus couteii-like microbe became abundant, while Acinetobacter johnsonii, Macellibacteroides fermentans, and Sedimentibacter acidaminivorans-like microbe were found as major bacteria for MP biofilm communities exposed to organic rich condition. The results of this study suggest that the unique freshwater biofilm community could be formed on the MP surface.